2005
DOI: 10.1111/j.1365-2133.2005.06533.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the 308-nm excimer laser and a 308-nm excimer lamp with 311-nm narrowband ultraviolet B in the treatment of psoriasis

Abstract: Both 308-nm light sources can clear patch psoriasis in a similar manner to standard phototherapy, with the advantage of the ability to treat exclusively the affected skin and with a reduced cumulative dose, thus perhaps reducing the long-term risk of carcinogenicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 14 publications
3
62
1
5
Order By: Relevance
“…These results agree with those of Kollner et al[ 11] in a recently published study. The sample size of the present study was rather small, and a significant difference of the two treatment modalities might have been observed in a larger cohort.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results agree with those of Kollner et al[ 11] in a recently published study. The sample size of the present study was rather small, and a significant difference of the two treatment modalities might have been observed in a larger cohort.…”
Section: Discussionsupporting
confidence: 83%
“…Considering the fact that the excimer laser selectively targets affected skin areas and that psoriatic lesions can tolerate much higher doses of UV light than adjacent healthy skin, we can assume that it is possible to observe faster and maybe even better clinical results using this newer monochromatic light delivery instead of narrow-band UVB phototherapy in the treatment of psoriasis. However, there are very few data comparing the clinical effects of narrow-band UVB and excimer laser treatment in psoriasis [11]. …”
Section: Introductionmentioning
confidence: 99%
“…These devices deliver high doses of UV radiation only to the psoriatic plaques and their use is accompanied by similar clinical response as conventional full-body phototherapy. 6,8,18,19 The use of high doses (several MEDs) is accompanied by a high incidence of short-term side-effects such as blister formation. Two independent studies reported that during treatment with the 308 nm excimer UVB laser, approximately 40% of patients developed blisters, some needing 7-14 days until complete healing.…”
Section: Discussionmentioning
confidence: 99%
“…6 This type of therapy regimens with targeted phototherapy are similar to those following conventional phototherapy. 8 The therapeutic effect of UVB radiation is mostly attributed to its immunosuppressive and immunomodulatory action. 9 The most important mechanism that explains the immunosuppressive effect of UV radiation is apoptosis induction.…”
Section: -5mentioning
confidence: 99%
“…Die Wirksamkeit dieser sog. gezielten ("targeted") UVB-Therapie mittels 308-nm-Excimer-Laser konnte für die Psoriasis hinlänglich in vielen Studien in den letzten Jahren nachgewiesen werden [10,16,30]. In der Mehrzahl der Studien kann bei ungefähr 80% dieser Patienten nach bis zu 12 Bestrahlungen eine vollständige Remission (Reduktion des PASI um ≥90%) erzielt werden [10,29,37].…”
unclassified